Dental Health Problems among the Patients Attending in the Orthodontic Department of Dhaka Dental College & Hospital (Bangladesh Journal of Dental Research & Education, 2013)
Objective: To know the prevalence & pattern of dental health problems among Bangladeshi people. Study design: Descriptive cross sectional study. Place of study: Department of Orthodontics & Dentofacial Orthopaedics of Dhaka Dental College & Hospital, Dhaka. Period of study: From September2011 to February2012. Sample selection: In this study, A total of 500 patients   (250 males & 250 females) were selected from Orthodontic department of Dhaka Dental College & Hospital. Results: This was a cross sectional study conducted among 500 patients attending at the department of Orthodontics and Dentofacial Orthopaedics, Dhaka Dental College and Hospital. Gingivitis was the commonest problem in Bangladeshi people according to present study. The second most dental problem was dental caries. The prevalence of orthodontic problems was comparable to the observations made by others. Males and females are equally affected with slight variations in the nature of problems among both genders. Conclusion: Good oral health is essential to improve individual overall health & well-being. We urge to take this information & use it for program planning & advocating for the health of patients, specially for the patients who will receive orthodontic treatment.  Therefore, current orthodontic students should receive more education & training before the management of malocclusion to improve the overall quality of care for orthodontic patients. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16608 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 19-25